Hubungan Karakteristik Pasien dan Daya Terima Makanan dengan Sisa Makanan pada Pasien Rawat Inap Depati Payung RSUD Mayjen HA Thalib Sungai Penuh - Maiken Dwi Vianera; Filius Chandra; Aisah Aisah (3031-8572, 2025)
Hospital nutrition services are crucial for supporting the recovery of inpatients, but a common problem is the amount of food waste left by patients. This study aimed to determine the relationship between patient characteristics (gender, age) and food acceptability with food waste at Mayjen H.A. Thalib Regional General Hospital, Sungai Penuh City. This descriptive quantitative study with a cross-sectional approach involved 43 patients selected using total sampling. Data were collected using questionnaires, checklists, and the Comstock scale for measuring food waste. Analysis was performed using the Chi-Square test, conducted from May 15 to June 11, 2025. Results showed that the majority of respondents were female (55.8%), with most in the early elderly category (46.5%). Most respondents had fair food acceptability (48.8%), and the majority left large amounts of food waste (74.4%). Analysis revealed that patient characteristics such as gender (p=0.423) and age (p=0.472) had no significant relationship with food waste. However, food acceptability had a significant relationship with food waste (p<0.000), indicating that better food acceptability resulted in less food waste